An Acid‐Regulated Self‐Blinking Fluorescent Probe for Resolving Whole‐Cell Lysosomes with Long‐Term Nanoscopy. Issue 21 (23rd March 2022) - Qiao, Qinglong; Liu, Wenjuan; Chen, Jie; Wu, Xia; Deng, Fei; Fang, Xiangning; Xu, Ning; Zhou, Wei; Wu, Shaowei; Yin, Wenting; Liu, Xiaogang; Xu, Zhaochao
Abstract: Long‐term super‐resolution imaging appears to be increasingly important for unraveling organelle dynamics at the nanoscale, but is challenging due to the need for highly photostable and environment‐sensitive fluorescent probes. Here, we report a self‐blinking fluorophore that achieved 12 nm spatial resolution and 20 ms time resolution under acidic lysosomal conditions. This fluorophore was successfully applied in super‐resolution imaging of lysosomal dynamics over 40 min. The pH dependence of the dye during blinking made the fluorophore sensitive to lysosomal pH. This probe enables simultaneous dynamic and pH recognition of all lysosomes in the entire cell at the single‐lysosome‐resolved level, which allowed us to resolve whole‐cell lysosome subpopulations based on lysosomal distribution, size, and luminal pH. We also observed a variety of lysosome movement trajectories and different types of interactions modes between lysosomes. Abstract : LysoSR‐549 as a self‐blinking fluorophore for SMLM imaging of lysosomes is reported. It enables simultaneous dynamic and pH recognition of all lysosomes in the entire cell at the single‐lysosome‐resolved level, which allowed to resolve whole‐cell lysosome subpopulations based on lysosome distribution, size, luminal pH, movement trajectories and interactions between lysosomes.